Pemberdayaan Pegawai Di Badan Kesatuan Bangsa Dan Perlindungan Masyarakat Provinsi Sulawesi Utara - MAMADOA, FENDY R; LALOMA, ALDEN; PLANGITEN, NOVVA N (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACTThis study aims to determine how Empowerment Of Employees In The Agency PublicProtection Of National unity North Sulawesi. The data collection was conducted throughinterviews with 8 informan consist of : 1 leadership of agency heads, 2 heads of field, 1head of sub fileds, 1 heads subpart, 3 staff. Based discussion Empowerment Of EmployeesIn The Agency Public Protection Of National unity North Sulawesi yet fully basedenabling and facilitating, but rather support by aspects conculting and collaborating.Therfore recommended that the Empowerment Of Employees adjustment need employeeswith different political,social,legal and national defense. And perform additionaloperational funds for stengthening the capacity of resource activities operatur, office alsoshould include more employees in training activities socialization according to the field ofwork that the task could be running properly.Keywords : Employee EmpowermentPENDAHULUANParadigma PemerintahDaerah yang